The relationship between parenting style and social responsibility of adolescents in Banda Aceh, Indonesia - Ansari, Afriani; Baharudin, Rozumah; Yaacob, Siti Nor; Deuraseh, Nurdeng @ Nurdeen (Universiti Putra Malaysia Press, 2012)
Theory and research have shown that parents have significant influence on their children’s social outcome. The present study was therefore conducted to determine the relationship between parenting style and social responsibility of adolescents residing in Banda Aceh, Indonesia. A total of 331 (male =119, female 212) students from four high schools in Banda Aceh were selected using Multistage Cluster sampling. The Indonesian version of Parental Authority Questionnaire (PAQ) and Social and Personal Responsibility Scale (SPRS) were used to measure parenting style and social responsibility, respectively. Findings showed that authoritarian and permissive parenting styles as significantly associated with improved adolescents’ social responsibility. Surprisingly, the study revealed no significant correlation between authoritative parenting style and adolescents’ social responsibility. The male adolescents in the study appeared to be more socially responsible than their female counterparts. Inconsistent with the other studies, the current study noted that non-authoritative parenting is positively related to adolescents’ social responsibility. Additionally, there may be variation in social responsibility by gender. The implication is discussed.